Transcatheter arterial embolization followed by octreotide and celecoxib synergistically prolongs survival of rabbits with hepatic VX2 allografts. Issue 1 (21st December 2012) - Tong, Huan; Li, Xiao; Zhang, Chun Le; Gao, Jin Hang; Wen, Shi Lei; Huang, Zhi Yin; Wen, Fu Qiang; Fu, Ping; Tang, Cheng Wei
<x xml:space="preserve">Abstract</x> Objective To validate the efficacy of an innovative multimodality therapy with transcatheter arterial embolization (TAE) plus octreotide and celecoxib in reducing neoangiogenesis and prolonging the survival of rabbits with hepatocellular carcinoma. Methods Rabbits with hepatic VX2 allografts were divided into four groups: control group, TAE group, octreotide + celecoxib (O + C) group and the multimodality therapy (TAE + O + C) group. Survival of the rabbits was analyzed using the Kaplan–Meier method and the expression of CD31 in tumor tissues was detected by immunohistochemistry. Results Rabbits in the TAE + O + C group lived nearly 20 days longer than those in the control group. The survival rate of the TAE + O + C group was 50% at day 80 and was the highest among the four groups (P < 0.05). No VX2 allograft‐bearing rabbits in the control group lived longer than 60 days. Compared with the control group, the survival time of the other two intervention groups were not prolonged significantly (P > 0.05). The CD31 expression induced by TAE was reduced significantly in TAE + O + C group (P < 0.05). Less metastasis was detected in TAE + O + C group. Conclusion TAE followed by the long‐term administration of octreotide and celecoxib can synergistically prolong the survival of rabbits with hepatic VX2 allografts by inhibiting potential neoangiogenesis, tumor growth and metastasis.